Research trends in CISTI's unveiled through text mining - Moro, S. (2018)
CISTI (Iberian Conference on Information Systems and Technologies) is a technical and scientific annual event dating back to 2006, whose purpose is to present and discuss knowledge, new perspectives, experiences and innovations in the Information Systems and Technologies domain (IST). The dynamics associated with IST together with the growing interest of the global community in CISTI have resulted in many topics and articles published in each conference, justifying a comprehensive analysis of the literature published. In this study, we present such analysis encompassing the last four editions, between 2013 and 2016, and a total of 677 articles. To accomplish such challenge more efficiently, we adopted text mining. We assessed through topic modeling how the unveiled research trends are aligned with the main conference themes. Data-driven empirical research has proven it is still a hot subject for researchers. Likewise, education and learning are also playing a significant role in CISTI's contributions. Notwithstanding, Internet and social media are highly relevant topics for the conference, although not figuring as major themes. On the other side, health is receiving less attention. Thus, this study can lead to recommendations for future CISTI's themes, in addition to providing an overview of current research trends.